Mapping SO₂ concentration distribution in South Sumatra Province: A sentinel-5p remote sensing approach - Ayu Arnita Putri; Vera Surtia Bachtiar; Yenni Yenni; Rahmat Wahyudi Putra (Journal of Environment and Sustainability Education, 2025)
Sulfur dioxide (SO2) is one of the main air pollutants that has a significant impact on human health and the environment, especially in areas with intensive industrial, mining, and transportation activities. South Sumatra Province as one of the provinces with quite massive industrial and mining activities, is a strategic area to study the spatial dynamics of SO2 concentration. This study pioneers the use of Sentinel-5P satellite remote sensing for high resolution spatio analysis of sulfur dioxide (SO₂) at the provincial level in Indonesia. Focusing in South Sumatra from 2021–2024, we quantified SO₂ dynamics across 17 regencies/cities. Results identified significant concentration SO2 in urban and industrial areas such as Palembang, Prabumulih, and Muara Enim, while agrarian areas such as North Musi Rawas and South OKU showed lower and more stable concentrations. Analysis revealed clear seasonal patterns, with dry seasons exhibiting elevated concentrations due to reduced atmospheric dispersion, and further linked fluctuations to post-pandemic economic recovery and land-use changes. Our findings demonstrate the critical value of Sentinel-5P as a tool for actionable air quality governance in Indonesia and underscore the importance of complementing satellite data with ground measurements for robust environmental policy.